The 1000 lumbar spine radiograph study - Pullicino, Glorianne; Pavia, Jessica; Sciortino, Paul; Chilmeran, Ahmed; Sciortino, Philip; Pullicino, Richard (International Journal of Medicine, 2017)
Magnetic resonance imaging is being increasingly used to optimize the diagnostic process for low back pain and to manage the risk of missing life-threatening pathology. The aim of the study was to examine the care pathway of low back pain with respect to the utilisation of CT and MRI service utilisation. A descriptive, retrospective, cross-sectional study was performed. A random sample of 1000 primary care patients presenting with low back pain who underwent lumbar spine radiography within a specified period was explored. 20% (n=198) of patients who underwent lumbosacral spine X-ray were referred for MRI investigation. Subsequently, 15 (7.6%) patients underwent joint infiltration whilst 6 (3%) patients underwent neurosurgical intervention during 2 years of follow-up. Such findings provide information for policy makers about the utility of MRI and CT scans.